Petrogenesis of late Cretaceous plutonic rocks and dykes in the eastern Southeastern Anatolian orogenic belt: Insights from geochemistry, zircon U-Pb-Hf isotope and trace element - Rizeli, Mustafa Eren (Pergamon-Elsevier Science Ltd, 2026)
This study presents an integrated petrographic, whole-rock geochemical, and zircon-based investigation of Late Cretaceous plutonic rocks and associated dykes exposed in the Koruko & uml;y area, northwest of Elaz & imath;g Province, T & uuml;rkiye. The aim is to constrain the magma source characteristics, emplacement conditions, and tectonic setting of these magmatic units within the framework of regional Late Cretaceous arc magmatism along the Southeastern Anatolian Orogenic Belt. The studied lithologies comprise diorite, granodiorite, granite plutons, as well as diabase dyke, diorite porphyry, tonalite porphyry, and aplitic dykes. Whole-rock geochemical data indicate that the rocks are metaluminous, I-type in character, and display tholeiitic to high-K calc-alkaline affinities. Trace element systematics and zircon Hf isotopic compositions (epsilon Hf(t) = +4.15 to +10.03; TDM = 507-881 Ma) indicate derivation from dominantly juvenile, mantle-derived magmas that experienced variable interaction with continental crust during magma storage and emplacement. The diabase dyke largely preserves mantle-dominated geochemical signatures, whereas the plutonic rocks record relatively stronger crustal influence. Ti-in-zircon thermometry indicates comparable crystallisation temperatures for the diorite and diabase dyke, whereas the tonalite porphyry records slightly lower temperatures, reflecting differences in magma composition and/or emplacement conditions. Zircon U-Pb ages of 80.92 +/- 0.64 Ma (diorite), 78.7 +/- 0.97 Ma (diabase dyke), and 80.48 +/- 0.48 Ma (tonalite porphyry) indicate a short-lived, multi-phase magmatic event during the Late Cretaceous. Integrated whole-rock and zircon geochemical data indicate that the Koruko & uml;y plutonic rocks and associated dykes formed in a continental arc setting related to northward subduction of the southern branch of the Neotethys Ocean, and represent part of the Late Cretaceous arc-related magmatic system developed along the Southeastern Anatolian Orogenic Belt.
Keywords: Late Cretaceous magmatism; Continental arc; Zircon U-Pb geochronology; Hf isotopes; I -type granitoids; Neotethys subduction